Avaliação histológica do tecido pulpar humano pósintrusão ortodôntica - Lazzaretti, Dieison Nardi (2013)
The forces applied during orthodontic treatment will cause effects on the teeth and adjacent tissues, depending on the intensity and time of application. Changes caused in the pulp tissues are not fully clarified in the literature by the scarcity of studies, the variety of methodologies, conflicting results and difficulty in conducting research that simulate clinical situations. Given this fact, the present study aimed to evaluate the human dental pulp after application of orthodontic intrusion force through histological examination. The selected sample consisted of 34 first human premolars, with orthodontic indication of extraction, from 17 young individuals (12-19 years old, both genders). On each patient, was applied intrusion force of 60g, randomly in only one of the dental elements, forming Group-Experimental (GE). The counterpart did not receive force, constituting the Control Group (CG), characterizing a split-mouth study. After 21 days, the premolars were extracted, stored in 10% formaldehyde, submitted to histotechnical preparation and stained with hematoxylineosin. The analysis of the histological slides was carried out in optical microscopy by a single experienced calibrated examiner. The paired Fisher exact test (p ≤ 0.05), showed significant increase of fibrous tissue in the GE. The nonparametric Wilcoxon test (p ≤ 0.05), paired, showed significant increase in the number of pulpal nodules in the elements of GE and showed no difference in the number of blood vessels between the groups. In 8 elements of the GE was observed the presence of congested large caliber vessels. The orthodontic intrusion force in these conditions, caused vascular changes in the pulp tissue, increase of fibrosis and of the number of pulpal calcifications in the experimental elements.